Clergy burnout : surviving in turbulent times - Lehr, J. Fred, 1946- (Fortress Press, 2022)
In Clergy Burnout: Surviving in Turbulent Times, Revised and Expanded, Fred Lehr explores the nature and practice of clergy codependence. In short, insightful, and easily accessible chapters filled with many examples and stories from his own life and the lives of those he has counseled, Lehr identifies the typical forms codependence takes in the life and ministry of clergy. These forms include the chief enabler, who keeps things functioning; the scapegoat, on whom everything that goes wrong is blamed; the hero, the example, the pure and righteous one; the lost child, whom no one really knows or cares about; the rescuer, who saves the day, fixes the problem, makes everything all right again; and the mascot, the cheerleader, the one who offers comic relief, brings down the tension level after a heated discussion. With a new preface, Lehr places the current challenges of ministry in the context of broader cultural shifts. The book concludes with a new chapter, Lehr's hard-won and carefully distilled words of wisdom for those who serve in turbulent times.